Blockchain based micropayment for e-health IOT sensors - Mahdi Shahraki; Amir Jalali Bighdeli (مدیریت مهندسی و رایانش نرم)
One of the valuable technologies that promises optimal solutions to many problems in the field of health care, etc., is the Internet of Things. Increasing the use of this technology in smart cities requires improving the IT infrastructure for the security and privacy of users. This has led to the use of blockchain technology alongside the Internet of Things. One of the applications of blockchain is its use in e-health, which is used to create a secure framework for managing patient records and to use its financial transactions to pay for services. The purpose of this article is to use one of the unique features of blockchain called micropayment to facilitate patient-related matters in e-health. This paper provides a framework for micropayments to pay for sensors and applications used to discuss patient health care in smart cities. The framework is designed to reduce the transaction fees of IoT users. It also reduces data processing, reduces the need for separate payment channels for each entity, and ultimately reduces payment time.